2014
DOI: 10.1103/physrevd.90.124062
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the evaporation of nonsingular black holes

Abstract: We present a model for studying the formation and evaporation of non-singular (quantum corrected) black holes. The model is based on a generalized form of the dimensionally reduced, spherically symmetric Einstein-Hilbert action and includes a suitably generalized Polyakov action to provide a mechanism for radiation back-reaction. The equations of motion describing self-gravitating scalar field collapse are derived in local form both in null co-ordinates and in Painleve-Gullstrand (flat slice) co-ordinates. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Let us mention that an independent interesting approach to the self-consistency problem are attempts to construct a regular black hole model in the framework of a 2D dilaton gravity, that include both quantum radiation and its back-reaction (see e.g. [59][60][61][62]. Anyway, search for (quantum) consistent nonsingular models of black holes is an interesting open problem which waits for its solution.…”
Section: Discussionmentioning
confidence: 99%
“…Let us mention that an independent interesting approach to the self-consistency problem are attempts to construct a regular black hole model in the framework of a 2D dilaton gravity, that include both quantum radiation and its back-reaction (see e.g. [59][60][61][62]. Anyway, search for (quantum) consistent nonsingular models of black holes is an interesting open problem which waits for its solution.…”
Section: Discussionmentioning
confidence: 99%
“…The Hamiltonian analysis of spherically symmetric ELL gravity was discussed in [41,42]. The following is based in large part on the methodology and results of [31,32] and uses the notation and conventions of [18].…”
Section: Hamiltonian Formalismmentioning
confidence: 99%
“…By making suitable choices of the functions of R in the action, the solutions can describe nonsingular spacetimes that have either two horizons or, at least in one special case, one horizon. If one chooses, for example, h(R) = V (R) = φ ,RR (R), the most general solution is [18]…”
Section: Criterion For Physical Nonsingular Black Holesmentioning
confidence: 99%
“…It is shown that other singularities such as big bang singularity [5] are modified considerably when quantum gravitational effects are considered. Similar considerations were applied to Black holes in several articles arguing that the collapse shall stop before the singularity is formed [3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. They either rely on arguments based on quantum gravity or Hawking radiation.…”
Section: Introductionmentioning
confidence: 99%